GORDON ALLPORT’S PSYCHOLOGICAL ANALYSIS IN THE MAIN CHARACTERS OF “MEMOIRS OF A GEISHA” BY ARTHUR GOLDEN - Alifatuz Zhain Intikah; Bambang Yulianto; Elisa Nurul Laili (Journal of Education, Linguistics, Literature and Language Teaching, 2020)
Abstract The novel "Memoirs of a Geisha" is the story of a woman who is educated, thoughtful, strong, and, most importantly, capable of true love. A literary work that contains many characters with different personalities which can be used as a reference in examining the personalities of several characters by using Gordon Allport's personality structure theory. This research is descriptive qualitative research with the data source of the novel “Memoirs of a Geisha” by Arthur Golden using codification. The technique of collecting data uses a literature study with four steps, namely reading, identifying, clarifying, and taking notes. In this study, there are three components in analyzing data, namely the data reduction, data display, and verification. The results of this study can be formulated that several figures have different traits, habits, and attitudes. Traits, habits, and attitudes are genetic and learning factors and each may precede or guide behavior. Keywords: Traits, Habits, and Attitudes of the main characters.